THE ROLE OF SUCCESSFUL MANAGEMENT IN QUALIFYING GRADUATE STUDENTS AND THEIR EXCELLENCE IN THE LABOR MARKET - Lect. Dr. Janat Reda Mohammed Al-Yasiri; Assist. Lecturer. Nadhir Mahdi Fadel (Scholar Express Journals, 2025)
Successful management in educational institutions, including universities, plays an important role in raising cognitive awareness by directly managing various service sectors and exerting efforts to technically, cognitively, and intellectually train graduates. Educational institutions serve as a key source for preparing and training young graduates and qualifying them for employment by understanding the challenges and difficulties they face in the workplace and how to develop solutions. The focus on youth has become one of the essential foundations of university education and successful management. Skills have become a fundamental factor for success as they are the only means to educate, distinguish, and enable graduates. These skills are acquired through years of training and work guided by successful management. The labor market can be considered a mental, intellectual, and neurological solution based on the efforts exerted by individuals to create material benefit for themselves and their families. This requires an educational system that prepares graduates capable of quickly adapting to the technical and technological changes witnessed worldwide.
Keywords: successful management, labor market, job qualification, integration of graduates into the labor market